2015
DOI: 10.1597/13-293
|View full text |Cite
|
Sign up to set email alerts
|

Academic Outcomes of Children with Isolated Orofacial Clefts Compared with Children without a Major Birth Defect

Abstract: Objective To compare academic outcomes between children with orofacial cleft (OFC) and children without major birth defects. Design and Setting In 2007–2008, we mailed questionnaires to a random sample of mothers of school-aged children with OFC and mothers of children without major birth defects (comparison group). The questionnaire included Likert-scale, closed-ended, and open-ended questions from validated instruments. We conducted bivariate and multivariable analyses on parent-reported educational outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 35 publications
1
37
0
Order By: Relevance
“…Two studies reported individuals with CL/P to have lower educational achievement than their peers without CL/P (Wehby, Collett et al, 2014;Knight et al, 2015) and elevated rates of academic difficulties (Snyder & Pope, 2010), particularly in the case of CPO (Persson, Becker & Svensson, 2012). In contrast, three studies found no significant differences in educational achievement between those with and without CL/P (Cheung, Loh & Ho, 2007;van der Plas et al, 2013;Collett et al, 2014).…”
Section: Educational Experiencesmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies reported individuals with CL/P to have lower educational achievement than their peers without CL/P (Wehby, Collett et al, 2014;Knight et al, 2015) and elevated rates of academic difficulties (Snyder & Pope, 2010), particularly in the case of CPO (Persson, Becker & Svensson, 2012). In contrast, three studies found no significant differences in educational achievement between those with and without CL/P (Cheung, Loh & Ho, 2007;van der Plas et al, 2013;Collett et al, 2014).…”
Section: Educational Experiencesmentioning
confidence: 99%
“…Chetpakdeechit and colleagues (2010) also reported a number of affected organ systems. One study reported that children with CL/P were significantly more likely to have a developmental delay than the control group (Knight et al, 2015). Developmental difficulties seemed to be more prevalent among types of cleft involving the palate (Chetpakdeechit et al, 2010;Burnell et al, 2014;Feragen et al, 2014).…”
Section: Associated Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This review identifies the sparsity of literature outlining motor speech, phonological and language abilities of individuals with nonsyndromic SMCP. Considering the emerging evidence suggesting language difficulties amongst the broader cleft lip and palate phenotype, investigations amongst the SMCP population appear timely and beneficial (Gallagher et al, ; Hardin‐Jones & Chapman, ; Klintö, Salameh, & Lohmander, ; Knight, Cassell, Meyer, & Strauss, ; Wehby et al, ; Young et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported increased dissatisfaction with speech and appearance and increased rates of peers' teasing among individuals with nonsyndromic OC (Marcusson et al, ; Hunt et al, ; Hunt et al, ). Some studies have also reported that children with nonsyndromic OC have lower academic performance on average (Persson et al, ; Wehby et al, ; Knight et al, ; Wehby et al, ), although such deficits have only been observed for children with CP in Denmark (Clausen et al, ). Because physical appearance, communication skills, and academic achievement play a major role in the social life and interaction with others, individuals with OC might be at risk of developing social problems, which might result in mental health problems.…”
Section: Introductionmentioning
confidence: 99%